KEPADATAN POPULASI HAMA KEPIK PENGHISAP BUAH (Helopeltis theivora) PADA TANAMAN KAKAO (Theobroma cacao L.) DI JORONG SIDUAMPAN KECAMATAN RANAH BATAHAN KABUPATEN PASAMAN BARAT - -, Afriyanti - (Pendidikan Biologi, 2014)
Cacao (Theobroma cacao L.) is of one the plantation commodity cultivated plantation by society in Jorong Siduampan Kecamatan Ranah Batahan Kabupaten Pasaman Barat. Plantation cacao is have a role in new work field supplying, farmer source of income and developing of region and also agroindustri. Growth in cacao plant can be pest attacked. The pest found is Helopeltis theivora and is of the one prominent pest is cacao plant the able to cause lower productivity him. Thing to the mentioned be based on reseach has been conducted about Population Density of Dented Pests Fruit of Inhalator (Helopeltis theivora) at cacao plant (Theobroma cacao L.) in Jorong Siduampan Kecamatan Ranah Batahan Kabupaten Pasaman Barat. This Research want to know population density of danted pests fruit of inhalator at cacao plant in Jorong Siduampan Kecamatan Ranah Batahan Kabupaten Pasaman Barat. This Research is a descriptive survey of research with total sampling method and use Chemical Knock Down technique, that is isolate mien animal or insect by pesticide of spraying Decis 25 EC. Research sample at removal all conducted of cacao fruit. Sample of conducted removal in Jorong Siduampan Kecamatan Ranah Batahan Kabupaten Pasaman Barat, conducted at morning at 07. 00 WIB at 10.00 WIB. From research of result which have to be got by density of mean Helopeltis theivora at nymph phase 1,33 individual/trunk and imago phase 0,64 individual /trunk. Population of density Helopeltis theivora at cacao plant in Jorong Siduampan Kecamatan Ranah Batahan Kabupaten Pasaman Barat 0,99 individual trunk each (sill economic not yet passed).